The Seductiveness of the interval : Romanian Pavilion - 53rd International Art Exhibition.La Biennale di Venezia 7th June - 22nd November 2009. Stefan Constantinescu, Andrea Faciu, Ciprian Muresan. - Bal, Mieke; Blyth, Alistair Ian; Barris, Roann; Bradeanu, Adina; Biennale Venetië 2009 (Stockholm : Romanian Cultural Institute of Stockholm, 2009)
Constantinescu, Stefan ; Faciu, Andrea ; Muresan, Ciprian
The Seductiveness of the interval, Romanian Pavilion, Venetië, 07.06.2009 - 22.11.2009.
kunstcatalogus
Keywords: Roemenië